Processes of consistency and contexts in free improvisation: preliminary approaches (Orfeu, 2017)
From research conducted in recentyears, I realized that despite the large number of studies devoted to the subject, freeimprovisation keeps today, a very broadand imprecise definition. In fact, there arecurrently in Brazil and in the world, manyartistic practices that include proceduresthat refer explicitly or not, to free improvisation. So one of the challenges that arisesis, on the one hand, the search for a definition of what would be common (especiallyin terms of sound materials and procedures) between multiple and diverse practices that are located in the vast territory offree improvisation or which make use of itand, second, what would be unique andspecific to each of these practices. Firstof all, it is necessary to establish whetherthere is actually a common territory thatcovers all these practices to further segment it into sub categories with their ownidentities. And more than that, it is necessary to unravel the building of consistencybuilding processes in each case. In this paper I intend to make a preliminary survey inview of the above outlined goals. I’m alsointerested in discussing to what extent andhow these various manifestations interactwith certain social, cultural and politicalcontemporary settings or, in other words,determine the extent to which free improvisation can be considered both as a symptom and as a line of force that contributes specifically to the setting of certain contemporary socio-cultural contexts relatedto creative practices.
Keywords: free improvisation; contexts; consistency processes